Deep transformations: A theory of degrowth - Hubert Buch-Hansen; Max Koch; Iana Nesterova (Manchester University Press, 2024)
As a research field, social movement and political project, degrowth is a multifaceted phenomenon. It brings together a range of practices including alternative forms of living and transformative initiatives in civil society, business and the state. Yet no comprehensive theory of degrowth transformations has so far been developed. Deep Transformations fills this gap. It develops a theory of degrowth transformations drawing on insights from multiple fields of knowledge, such as political economy, sociology and philosophy. The book offers a holistic perspective that brings into focus transformation processes on various scales and points to various mechanisms that can facilitate degrowth. These include, for instance, eco-social policies, transformative initiatives in business and civil society and alternative modes of being in and relating with the world.
Keywords: 330; degrowth; capitalism; sustainability; critical realism; deep transformations; eco-social policies; state; business; civil society; political economy